Aerobic Co or Cu/NHPI-catalyzed oxidation of hydride siloxanes: synthesis of siloxanols. Issue 7 (14th March 2018) - Arzumanyan, Ashot V.; Goncharova, Irina K.; Novikov, Roman A.; Milenin, Sergey A.; Boldyrev, Konstantin L.; Solyev, Pavel N.; Tkachev, Yaroslav V.; Volodin, Alexander D.; Smol'yakov, Alexander F.; Korlyukov, Alexander A.; Muzafarov, Aziz M.
Abstract : An efficient preparative method for the synthesis of siloxanols based on aerobic Co(OAc)2 or Cu(OAc)2 /NHPI-catalyzed oxidation of hydride siloxanes has been proposed. Abstract : A highly efficient preparative method for the synthesis of siloxanols based on aerobic Co(OAc)2 or Cu(OAc)2 /NHPI-catalyzed oxidation of hydride siloxanes using "green", commercially available, simple inexpensive reagents and mild reaction conditions has been proposed. This is a general reaction for the synthesis of mono-, oligo- and polymeric siloxanols with various structures (linear, branched and cyclic).